Calm in Calamity: Tafakur as Psychospiritual Intervention for University Students Dealing with Emotional Stress - Nur Yani, Che Hussin; Muhammad Nubli, Abdul Wahab (UnIPSAS, 2023)
Emotional wellbeing is the most crucial factor figuring out the student’s success. The impact of stress that can affect a student’s mental health has appeared as a major issue and is reaching alarming proportions. This study examines the use of tafakur technique as a psychospiritual intervention in coping with emotional stress among university students. The treatment and control group were made up of thirty university students. Tafakur intervention programme was linked to lower stress, anxiety, and depression after four weeks. Therefore, the tafakur technique is the best alternative mechanism used as a psychospiritual intervention in dealing with emotional stress among university students.